Differentially methylated CpG island within human XIST mediates alternative P2 transcription and YY1 binding - Chapman, Andrew G (BMC Genet, 2014)
BACKGROUND: X-chromosome inactivation silences one X chromosome in females to achieve dosage compensation with the single X chromosome in males. While most genes are silenced on the inactive X chromosome, the gene for the long non-coding RNA XIST is silenced on the active X chromosome and expressed from the inactive X chromosome with which the XIST RNA associates, triggering silencing of the chromosome. In mouse, an alternative Xist promoter, P2 is also the site of YY1 binding, which has been shown to serve as a tether between the Xist RNA and the DNA of the chromosome. In humans there are many differences from the initial events of mouse Xist activation, including absence of a functional antisense regulator Tsix, and absence of strictly paternal inactivation in extraembryonic tissues, prompting us to examine regulatory regions for the human XIST gene. RESULTS: We demonstrate that the female-specific DNase hypersensitivity site within XIST is specific to the inactive X chromosome and correlates with transcription from an internal P2 promoter. P2 is located within a CpG island that is differentially methylated between males and females and overlaps conserved YY1 binding sites that are only bound on the inactive X chromosome where the sites are unmethylated. However, YY1 binding is insufficient to drive P2 expression or establish the DHS, which may require a development-specific factor. Furthermore, reduction of YY1 reduces XIST transcription in addition to causing delocalization of XIST. CONCLUSIONS: The differentially methylated DNase hypersensitive site within XIST marks the location of an alternative promoter, P2, that generates a transcript of unknown function as it lacks the A repeats that are critical for silencing. In addition, this region binds YY1 on the unmethylated inactive X chromosome, and depletion of YY1 untethers the XIST RNA as well as decreasing transcription of XIST.